2018
DOI: 10.1017/wet.2018.84
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Herbicide Particle Drift: Effect of Hooded Sprayer and Spray Quality

Abstract: A field study was conducted in 2015 and 2016 to compare particle drift of glyphosate using a fluorescent tracer dye applied with hooded and open sprayers at four spray qualities (Fine [F], Medium [M], Very-Coarse [VC], and Ultra-Coarse [UC]). F and M spray qualities exhibited up to 86% and 56% less drift, respectively, out to 31 m downwind with the hooded sprayer than with the open sprayer. Conversely, VC and UC spray qualities were not affected by sprayer type out to 31 m downwind. From 43 to 104 m downwind, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 42 publications
3
38
0
Order By: Relevance
“…Preventing resistance-prone weeds on field margins is an important best management practice (BMP) to delay herbicide resistance, although the additional management costs and time constraints pose a challenge for growers [18,62]. Growers should consider additional strategies to mitigate near-field spray drift [43,63], and implement appropriate control strategies to manage weed populations on field borders, such as mowing, using boomless nozzles for weed control in areas of difficult access (fencerows, electrical lines), or planting and maintaining field borders to a less-weedy and easier to manage species [37].…”
Section: Resultsmentioning
confidence: 99%
“…Preventing resistance-prone weeds on field margins is an important best management practice (BMP) to delay herbicide resistance, although the additional management costs and time constraints pose a challenge for growers [18,62]. Growers should consider additional strategies to mitigate near-field spray drift [43,63], and implement appropriate control strategies to manage weed populations on field borders, such as mowing, using boomless nozzles for weed control in areas of difficult access (fencerows, electrical lines), or planting and maintaining field borders to a less-weedy and easier to manage species [37].…”
Section: Resultsmentioning
confidence: 99%
“…Preventing the establishment of resistance prone weeds on field margins and ditches in agricultural landscapes is an important management strategy to delay herbicide resistance, especially for cross-pollinated weed species such as Palmer amaranth and waterhemp 16,75 . Weed management programs should consider strategies to mitigate near-field spray drift, and suppress weed populations on field borders and ditches in agricultural landscapes 16,62,75,76 . Figure 6.…”
Section: Populationmentioning
confidence: 99%
“…Roten et al [32] and Foster et al [33] showed that the use of low-drift nozzles resulted in a reduction of drift in the range from 81% to 94% compared to control nozzles (standard ones). As it is clear from the analyses carried out by these researchers, the precise application of herbicides is possible using a shield, ensuring cooperation with the appropriate type of sprayer.…”
Section: Discussionmentioning
confidence: 99%